THE PARTITIONING OF NA BETWEEN MELILITE AND LIQUID: PART II. APPLICATIONS TO TYPE B INCLUSIONS FROM CARBONACEOUS CHONDRITES - Beckett J.R.; Simon S.B.; Stolper E. (My University, 2000)
The zoning of Na in the melilite of Type B1 Ca-, Al-rich inclusions from carbonaceous chondrites reflects a combination of factors including the maximum temperature, Tmax, for melting, bulk composition, crystal dimensions and the degree of diffusive relaxation. We used experimentally determined partition coefficients for Na between melilite and liquid together with modes and compositions of phases in meteoritic inclusions to calculate Na zoning produced in melilite by crystallization from Na-bearing liquids. We then used a simple model for the diffusive relaxation of an originally igneous zoning profile to constrain the thermal history. For Allende Type B1 inclusion TS-34, the melilite compositions are consistent with an initial melting event (Tmax ~ 1450°C) during which essentially Na-free melilite crystallized, followed by the introduction of Na during a hiatus, a second melting event with Tmax ~ 1290°C in which Na-bearing melilite with XAkMel =< 0.47 grew on relict cores of melilite from the first melting event, and partial diffusive relaxation. For the Type B1 inclusion Vigarano 1623-8, previously published bulk and melilite compositions lead to the conclusion that Tmax did not exceed ~1280°C during the last major melting event. A survey of literature data for other inclusions suggests that Na zoning in melilite may be a generally useful indicator of thermal history and that Type B1 inclusions were commonly subjected to multiple melting events with intervening periods of alteration.At any given value of XAkMel in TS-34, calculated melilite/liquid partition coefficients for Na are lower than values determined experimentally for melilite of similar composition because of liquid composition effects. The difference is more than a factor of two for XAkMel > 0.5, and it is likely, based on the activities of major oxides in the melt, that liquid composition effects are also important for other elements. On the other hand, modeling of diffusive relaxation for Na in melilite suggests that the diffusion coefficients are not strongly dependent on either XAkMel or Na concentration.